OPPORTUNITIES AND CHALLENGES OF THE IMPLEMENTATION OF ISLAMIC LAW IN INDONESIA - Samsidar Jamaluddin; Muhrim Djakat; Hidayatussalam Hidayatussalam; Sabri Samin; Misbahuddin (Bajang Institute, 2023)
Islamic law only became an authoritative source (a legal source that has legal force) in constitutional law when the Jakarta Charter was placed in the Republic of Indonesia's Presidential Decree dated 5 July 159 as can be seen in the preamble to the Decree as follows: